Acceptance as a possible link between past psychedelic experiences and psychological flexibility - Krabbe, Andreas; Sikka, Pilleriin; Jylkkä, Jussi (Springer Nature, 2025)
Increased psychological flexibility (PF) may underlie the lasting positive effects of psychedelic experiences on mental well-being. The associations between different components of PF, psychological inflexibility (PI), and well-being with psychedelic use are not well understood. We conducted a cross-sectional internet survey of participants (N = 629) with experience of classical psychedelics. Using network analysis, we examined how aspects of a single psychedelic experience (mystical-type features and psychological insights) and the frequency of past psychedelic use, were associated with current PF and PI components, as well as with mental well-being and ill-being. Mediation analyses explored whether PF mediated the relationship between past psychedelic use and well-being or ill-being. The network analysis linked psychological insight to the PF component Acceptance, with no association found between the frequency of past use and PF. Mediation analyses showed PF mediates the association between past psychedelic use and well-being and ill-being. These results suggest that the quality and depth of the psychedelic experience, rather than the frequency of use, are primarily linked to psychological flexibility, particularly Acceptance, and overall well-being. This underscores the importance of treating PF as a multidimensional construct to better understand the long-term mental health benefits of psychedelics. © The Author(s) 2024.